Evaluating factors affecting the readiness of children entering elementary school: the perspective of elementary school teachers - Izzanil Hidayati; Meria Susanti; Nila Anggreiny; Yantri Maputra (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
Children who are ready to participate in learning at elementary school can be seen from various components, namely basic abilities, social, emotional, communication, age, and independence. This study aims to determine the problems that exist in children when entering elementary school.  This study used a quantitative method with a descriptive quantitative design. The subjects in this study are 104 elementary school teachers (84 public; 20 private). The measuring instrument in this study uses an open questionnaire containing questions about the problems encountered by elementary school teachers regarding the readiness of children to enter elementary school. The results showed that the problems encountered by primary school teachers who teach first-grade students in terms of school readiness could be divided into three categories: (1) basic abilities of children refer to a child's abilities that can support independence in learning (cognitive); (2) social abilities are defined by a child's ability to form friendships with classmates, collaborate, and play with peers; and (3) parental support associated with the presence of parents in accompanying the child's learning process and meeting the child's psychological needs and facilities. Thus, children who are ready for school are assessed from their cognitive abilities and other important aspects.